Beyond Bedlam : poems written out of mental distress - Post, Felix; Smith, Ken, 1938-2003; Sweeney, Matthew, 1952-2018 (London : Anvil Press Poetry, 1997)
De titel is duidelijk: een bundeling gedichten die allemaal hun oorsprong vinden in mentale problemen die de auteurs mochten ervaren. In deze bundel ook outsiderkunst uit het bekende Royal Bethlem and Maudsley Hospital Archive & Museum.
Keywords: English poetry -- 20th century; Mental illness -- Poetry; Mentally ill, Writings of the, English